2020
DOI: 10.3389/fnut.2019.00196
|View full text |Cite
|
Sign up to set email alerts
|

Biologically-Based Complementary and Alternative Medicine (CAM) Use in Cancer Patients: The Good, the Bad, the Misunderstood

Abstract: As complementary and alternative medicine (CAM) becomes more popular, it is being used in cancer patients to aid in recovery or to treat symptoms associated with the current chemotherapy. Numerous papers exist that discuss patients using CAM with cancer chemotherapy and their outcomes-both positive and negative. However, in the case of the negative outcomes, the reason for the dangers or interactions with drugs are not made clear. Indeed, many chemotherapy regimens are rendered less effective by the well-meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 69 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…This may lead to subtherapeutic drug levels as well as to prolonged activity and even toxicity of a drug [ 14 , 30 ]. On the pharmacodynamics effect, antioxidant supplements could interfere with radiation or with any chemotherapy that operates via a free radical mechanism [ 31 , 32 ]. For instance, vitamin E and beta-carotene reduce toxicity from radiotherapy among patients with head and neck cancer, and hence it has been found to increase recurrence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to subtherapeutic drug levels as well as to prolonged activity and even toxicity of a drug [ 14 , 30 ]. On the pharmacodynamics effect, antioxidant supplements could interfere with radiation or with any chemotherapy that operates via a free radical mechanism [ 31 , 32 ]. For instance, vitamin E and beta-carotene reduce toxicity from radiotherapy among patients with head and neck cancer, and hence it has been found to increase recurrence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to cancer treatments, roughly half of the patients receiving treatment use CAM [ 55 ]. Patients decide to use alternative medicine alongside chemotherapy for many reasons including strengthening of the immune system, improving well-being, and relieving symptoms of either the disease or disease treatment, such as nausea, insomnia, and pain [ 56 ]. Publications evidencing positive and negative effects of the use of herbs with chemotherapy abound.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study revealed a reduction in the overall CAM use, there are very noticeable changes in the trend that are worth paying attention to. This trend of reduction in using CAM maybe due to more physician opposing the use of CAM as well as increased awareness of both of the public and the healthcare professionals of the potential harm of some of the CAM, due to interaction with the medications or the inherent side effects of CAM or avoiding getting treatment [16][17][18].…”
Section: Discussionmentioning
confidence: 99%